Teachers and Curriculum Materials in the Teaching of Social and Natural Sciences. An Analysis on Andalusian Teachers' Beliefs and Reflective Practice (Spain) - Gabriel Travé-González; Francisco José Pozuelos-Estrada; Antonio Soto-Rosales (Arizona State University, 2015)
The results of an investigation into teachers´ conceptions on the use of curricular materials (textbooks and teacher-developed materials) in the teaching of Social and Natural sciences are presented. The study explores teachers´ representations on the processes of design, management and evaluation of the materials in order to propose improvements in classroom practices and educational policies. The research design is based on the application of mixed methods using questionnaires and interviews administered to a sample of Andalusian teachers (Spain). Among the findings it is emphasized the teachers´ ignorance about the fee-free policy and the experimentation of the textbooks, the poor teacher training for the development of curriculum materials; and finally, the need to reconcile tradition and innovation in future materials.